Leadership and Pedagogical Interaction as Predictors of Learning Outcomes in Physical Education - Araújo, Pedro Trigo (2017)
Problem Statement: This research aims to understand the relative contribution of leadership styles and teacher-student and student-student pedagogical interaction concerning the learning performance and academic achievement in physical education. Research Questions: Are the teacher leadership style and the teacher-student and student-student pedagogical interaction related to the learning performance and academic achievement in physical education in basic schooling? Purpose of Study: There are several factors that contribute for the explanation of learning outcomes, namely teacher leadership styles in the classroom, as well as teacher-student and student-student pedagogical interactions. These factors are considered to be essential in the teaching-learning process and in the subsequent improvement of educational outcomes. Research Methods: A quantitative methodology was implemented, comprising a sample of 447 students attending a School Grouping located in the Central Region of Portugal. In order to verify the nature, the strength and the direction of the relations among the variables, correlation and multiple regression analyses were used. For this, scales already validated and used in other researches were applied. Findings: The results show that the learning performance and the academic achievement are significantly associated with teacher leadership styles and teacher-student and student-student pedagogical interaction. A stronger association was obtained with leadership styles, especially the democratic one. It should be mentioned that these factors provide a higher relative contribution to the learning performance than to the academic achievement. Conclusions: This study sought to deepen the understanding of the explanatory factors of academic success concerning the teaching-learning process in physical education. The analysis conducted highlights the importance of the democratic teacher leadership style and of the pedagogical interaction established within the classroom towards the improvement of students' ability to understand the gains and the effort made in learning.